KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH MOMODERASI PENGARUH KOMPETENSI PROFESIONAL, KOMPETENSI PEDAGOGIK, DAN KOMPETENSI SOSIAL TERHADAP KINERJA GURU (STUDI PADA GURU SMK NEGERI SUB RAYON 01 KOTA SEMARANG) - 11.52.02.0137, Sambiyono (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this research is to examine and analyze the influence of pedagogical competence, professional competence, and social competence to teachersâ performance as variables which are considered influencing the transformational leadership of principals. In addition, those variables are considered being influenced by Teachersâ performance of State Secondary Vocational Schools in Regional Area of Rayon 01 Semarang.The samples taken for this research were 141 teachers of official and non official servants of State Secondary Vocational Schools in Regional Area of Rayon 01 Semarang. The overall population is 242 teachers. The method used in collecting data was questionnaires based on Likert Scale with the range from 1 to 7. The data was primary data; it means that this research used respondentsâ answers to the questionnaires. Multiple linear regressions were used as statistical technique in processing the data.The result of the study shows that (H1) the lower of teachersâ pedagogical competence the higher of teachersâ performance competence. Consequently, the first hypothesis is rejected. The second hypothesis is (H2), the higher of teachersâ professional competence the higher of teachersâ performance competence. This hypothesis is accepted. The third hypothesis is (H3), the teachersâ social competence is rejected. The fourth hypothesis is (H4) transformational leadership did not have influence the teachersâ performance competence, rejected. The fifth hypothesis (H5) is transformational leadership weakens the influence of pedagogical competence and teachersâ performance relationship. The sixth hypothesis (H6) is the influence of teachersâ professional competence is weakened by transformational leadership of principals. This influence is called weakening moderation. The seventh hypothesis (H7) is moderated-influence between social competence and teachersâ performance is rejected. In general, it can be concluded that the three independent variables and one moderating variable clarified 54,9% the teachersâ performance and the rest were explained by other factors that were not concerned in this research. Keyword: transformational leadership of principals, pedagogical competence, professional